Pengolahan Limbah Plastik Menjadi Hiasan Kreatif: Upaya Edukasi Pengurangan Sampah dan Pemberdayaan Ekonomi Masyarakat di Desa Perampuan, Lombok Barat - Sanuriza, Irna Il; Jayadi, Irfan; Ihwan, Khaerul; Husain, Pahmi; Risfianty, Dwi Kartika; Atika, Baiq Naili Dewi; Alyaminy, Ishmah Humaidatul Aminah Zaim; Dewi, Irma Risvana; Amanda, Vera Junita; Atqia, Tilawatul; Anita, Anita (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
Household plastic waste becomes an increasingly serious environmental problem if not managed properly. This community service activity aims to improve public knowledge, skills, and awareness in managing plastic waste through training in making creative decorations based on recycling. Participants in the activity were housewives and youth in Perampuan Village, Labuapi District, West Lombok Regency. The implementation method uses an experiential learning approach through stages of socialization, environmental education, introduction to recycled product innovations, training in making decorations, and evaluation and reflection. The results of the activity showed high enthusiasm from the participants, where all participants succeeded in producing at least one type of decoration independently. As many as 90% of participants showed an increase in understanding of the impact of plastic waste and the principles of 3R management. In addition to mastering technical skills, this activity also gave rise to creative economy-based entrepreneurial ideas from some participants. This community service activity provides a positive contribution in building environmental awareness, empowering the community economically, and supporting community-based plastic waste management efforts.